Preparing future physicians for complexity: a post-graduate elective in HIV psychiatry - Deanna Chaukos; Sandalia Genus; Robert Maunder; Maria Mylopoulos (BMC Medical Education, 2023)
Abstract Background Patients with complex care needs have multiple concurrent conditions (medical, psychiatric, social vulnerability or functional impairment), interfering with achieving desired health outcomes. Their care often requires coordination and integration of services across hospital and community settings. Physicians feel ill-equipped and unsupported to navigate uncertainty and ambiguity caused by multiple problems. A HIV Psychiatry resident elective was designed to support acquisition of integrated competencies to navigate uncertainty and disjointed systems of care – necessary for complex patient care. Methods Through qualitative thematic analysis of pre- and post-interviews with 12 participants – residents and clinic staff – from December 2019 to September 2022, we explored experiences of this elective. Results This educational experience helped trainees expand their understanding of what makes patients complex. Teachers and trainees emphasize the importance of an approach to “not knowing” and utilizing integrative competencies for navigating uncertainty. Through perspective exchange and collaboration, trainees showed evidence of adaptive expertise: the ability to improvise while drawing on past knowledge. Conclusions Postgraduate training experiences should be designed to facilitate skills for caring for complex patients. These skills help residents fill in practice gaps, improvise when standardization fails, and develop adaptive expertise. Going forward, findings will be used to inform this ongoing elective.